Change in Religious Understanding and Language Shift of the Recitations of the Quran and Hadith in the Perspective of Islamic Jurisprudence - Ushalli, Eskarni; Salma; Hayati, Naila; Yuherlis, Neni; Kirin, Arwansyah (GoAcademica Research & Publishing, 2024)
This writing aims to analyze the occurrence of changes in the understanding of the community and the shift in language of some recitations of the Quran and Hadith from the perspective of Islamic jurisprudence (fiqh). Understanding religion cannot be separated from the issue of language shift because the fundamental sources of Islamic teachings are the Quran and Hadith, both of which are in Arabic. The translation of verses from the Quran and Hadith into the Indonesian language is not without uncertainties. For example, the change in understanding of the word